Analysis and Prospects of the Digital Economy in Russia. Issue 1 (September 2020) - Konnikov, Evgenii; Dubolazova, Yulia; Konnikova, Olga; Malevskaia-Malevich, Ekaterina
Abstract: The beginning of the 21 st century saw the development of digital technologies due to the information revolution and globalization processes. Information has become a principal resource in the society and business processes. A person can transform it into knowledge and social and economic relationships are migrating into the network space. The digital culture is a key factor of the digital transformation. Comprehensive introduction of state-of-the-art digital technologies is one of the growth areas for the economy as they change business processes, communications and the social sphere and, as a result, create the new "digital" culture. The authors of this paper focus on the fact that in the nearest future the majority of technologies will be developed at the intersection of various interrelated industries, from 3D printers to cloud computing and mobile applications. The paper also explores the ways various governments deal with the changes resulting from the digital economy and the costs they incur to arrange the interaction of citizens with public authorities using various digital technologies. These and other factors make the article relevant. The subject matter of the paper is digital technologies, which are crucial for Russia's economic development. The goals include the research of the state of the digital economy in Russia and in the world, analysis of the digital economy program as a priority for the country's economic development and determination of the economic digitalization prospects. The research is based on such methods as examination and generalization, analysis and synthesis, as well as comparative analysis, which made it possible to specify basic digital economy trends.